Study on Anaerobic Digestion and the Treatment of Livestock and Poultry Waste Liquid by Nanoparticles and Antibiotics in the Context of Carbon Neutrality and Microbial Ecosystems - Xiaofei Zhen; Han Zhan; Ke Li; Ruonan Jiao; Lei Feng; Tie Du (Agronomy)
Livestock and poultry waste liquid contains a lot of nitrogen, phosphorus, and microorganisms, and direct discharge causes great harm to the environment. Chicken manure was selected as the research object, and nanoparticle nano-Fe2O3, nano-C60, antibiotics enrofloxacin, sulfamethoxazole, and oxytetracycin were selected as additives to carry out medium-temperature sequential batch anaerobic digestion experiment. The experiment lasted for 55 days. The results showed that (1) gas production reached its peak in the first 1–2 days of a single stress experiment, and the cumulative gas production in the first 10 days was as follows: R5 > R4 > R3 > R2 > CK > R1; (2) the concentrations of total volatile fatty acids (TVFAs) in the groups increased rapidly from day 1 to 10, and the concentrations of TVFAs in the nano-Fe2O3 and nano-C60 groups were higher than those in the other four groups. The pH of the system decreased, and the soluble chemical oxygen demand (SCOD) was consistent with the trend of TVFAs, while the pH of the nanoparticle group was lower; (3) changes in the horizontal structure of bacterial community of Firmicutes and Bacteroidetes were dominant bacteria in each group on the first day. On day 5, the relative abundance of actinomycetes and Bacteroidetes increased significantly. This experiment contributes to the study of the effects of adding nanoparticles and antibiotics to anaerobic digestion substrates on gas production characteristics, provides data support, and characterizes the microbial situation during digestion. This paper can help to realize carbon emission reduction in agriculture and rural areas. Based on the above background, a self-designed system for testing the anaerobic digestion potential of methane was used in this study using chicken manure. Based on the single pollutant stresses of nano-Fe2O3, nano-C60, enrofloxacin, sulfamethoxazole, and hygromycin, the effects of different pollutants under independent stresses on methane production and the changes in the performance of the anaerobic digestion system for gas production were investigated. The chemical parameters and microbial diversity in the anaerobic digestion process were analyzed, and the effects of different nanoparticles and antibiotics on the anaerobic system of chicken manure were elucidated. The results of the study can provide data support for the stable operation of biogas projects, which is of great significance in promoting the sustainable development of ecological agriculture.